The Global, Regional, and National Burden of Psoriasis: Results and Insights From the Global Burden of Disease 2019 Study - Damiani, Giovanni; Bragazzi, Nicola Luigi; Karimkhani Aksut, Chante; Wu, Dongze; Alicandro, Gianfranco; McGonagle, Dennis; Guo, Cui; Dellavalle, Robert; Grada, Ayman; Wong, Priscilla; La Vecchia, Carlo; Tam, Lai-Shan; et al. (Frontiers in Medicine, 2021)
Background: Psoriasis is a common, chronic, inflammatory, debilitating, systemic disease with a great impact on healthcare systems worldwide. As targeted therapies have transformed the therapeutic landscape, updated estimates of the Global Burden of Disease (GBD) imposed by psoriasis are necessary in order to evaluate the effects of past health care policies and to orient and inform new national and international healthcare strategies. Methods: Data were extracted from the GBD 2019 study, which collates a systematic review of relevant scientific literature, national surveys, claims data, and primary care sources on the prevalence of psoriasis. Prevalence data were combined with disability weight (DW) to yield years lived with disability (YLDs). Measures of burden at global, regional, and national levels were generated for incidence, prevalence, and YLDs, due to psoriatic disease. All measures were reported as absolute numbers, percentages, and crude and age-adjusted rates per 100,000 persons. In addition, psoriasis burden was assessed by socio-demographic index (SDI). Findings: According to the GBD 2019 methodology, there were 4,622,594 (95% uncertainty interval or UI 4,458,904–4,780,771) incident cases of psoriasis worldwide in 2019. The age-standardized incidence rate in 2019 was 57.8 (95% UI 55.8–59.7) per 100,000 people. With respect to 1990, this corresponded to a decrease of 20.0% (95% UI −20.2 to −19.8). By sex, the age-standardized incidence rate was similar between men [57.8 (95% UI 55.8–59.8) per 100,000 people] and women [(57.8 (95% UI 55.8–59.7) per 100,000 people]. With respect to 1990, this corresponded to a decrease by 19.5% (95% UI −19.8 to −19.2) and by 20.4% (95% UI −20.7 to −20.2) for men and women, respectively. The age-standardized incidence rate per 100,000 persons was found to vary widely across geographic locations. Regionally, high-income countries and territories had the highest age-standardized incidence rate of psoriasis [112.6 (95% UI 108.9–116.1)], followed by high-middle SDI countries [69.4 (95% UI 67.1–71.9)], while low SDI countries reported the lowest rate [38.1 (95% UI 36.8–39.5)]. Similar trends were detected for prevalence and YLDs. Conclusion: In general, psoriasis burden is greatest in the age group of 60–69 years, with a relatively similar burden among men and women. The burden is disproportionately greater in high-income and high SDI index countries of North America and Europe. With advances in psoriasis therapeutics, objective evaluation of psoriasis disease burden is critical to track the progress at the population level.